2000
DOI: 10.1101/lm.32600
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Responses to LTP Induction in the Rat Hippocampus: A Comparison of In Vitro and In Vivo Techniques

Abstract: Because exogenous application of a number of cytokines and growth factors can alter synaptic properties, we sought to determine if endogenous cytokine expression is affected by neuronal activity. In addition, we examined whether cytokine expression is altered by the techniques used to stimulate and record from hippocampal neurons. Using semi-quantitative RNase protection and RT-PCR assays, we studied the expression of 18 cytokine, growth factor, and receptor genes in the hippocampus following the induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 48 publications
0
60
0
Order By: Relevance
“…Further, we have observed that the IL-6 gene is also over expressed during in vivo and in vitro LTP [5,6]. Other laboratories have confirmed these results [7]. More recently, we have detected that IL-1 receptor antagonist (IL-1ra) but not TNFa, is induced during LTP in freely moving rats (manuscript submitted).…”
Section: Increased Neuronal Activity Results In Il-1 and Il-6 Expressmentioning
confidence: 62%
“…Further, we have observed that the IL-6 gene is also over expressed during in vivo and in vitro LTP [5,6]. Other laboratories have confirmed these results [7]. More recently, we have detected that IL-1 receptor antagonist (IL-1ra) but not TNFa, is induced during LTP in freely moving rats (manuscript submitted).…”
Section: Increased Neuronal Activity Results In Il-1 and Il-6 Expressmentioning
confidence: 62%
“…A considerable body of experimental and clinical evidence suggests that IL-1β, IL-6, and TNF-α are induced by seizure activity and that these cytokines contribute to the formation of structural changes, such as neuronal damage and gliosis, after sustained seizure activity (49)(50)(51). Interestingly, in patients with recent generalized tonic-clonic seizures, the IL-6 level was selectively elevated in cerebrospinal fluid (CSF) and plasma without any change in IL-1β and TNF-α levels (52), and the elevated plasma IL-6 level was correlated with peripheral blood leukocyte counts and CRP (53).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it must be noted that cytokines interact in a network where the function of one cytokine can be modified, modulated or substituted by others [42]. It has been hypothesized that IL-6 has an opposite role to IL-1 in synaptic plasticity and LTP maintenance, by inducing negative feedback and inhibiting the effects of IL-1 on LTP maintenance [6,38] and/or by curtailing synaptic improvement at neighboring synapses [43].…”
Section: Id Patients Controlsmentioning
confidence: 99%